Consistent negative response of US crops to high temperatures in observations and crop models - Bernhard Schauberger (Nature Portfolio, 2017)
Future agricultural productivity is threatened by high temperatures. Here, using 9 crop models, Schaubergeret al. find that yield losses due to temperatures >30 °C are captured by current models where yield losses by mild heat stress occur mainly due to water stress and can be buffered by irrigation.